(514) National Budgeting in Polish Practice الميزانية الوطنية في الممارسة البولندية - Z. Fedorowicz, Zdzislaw (INP, 2024)
The study discusses the concept of "national budgeting" in Polish practice, noting that it is not a term used in Polish planning or in any other socialist country. However, this term has gained widespread use in global economic literature over the past twenty years, referring to financial plans related to the future or financial reports concerning the past. In Poland, the role of the national budget is fulfilled by two aggregate financial plans accompanied by supplementary tables detailing certain items. Annual national budgets are closely linked to annual national economic plans, fully reflecting physical plans such as the creation and allocation of national income. These plans also include annual operational budgets and credit plans.